Influence of soil tillage methods and fertilization systems on winter wheat yield - Саюк, О. А.; Плотницька, Н. М.; Павлюк, І. О.; Ткачук, В. П. (Scientific Progress & Innovations, 2018)
Influence of soil tillage methods and fertilization systems on yield of winter wheat variety Kolos Myronivshchyny in the conditions of Polissia in Ukraine has been investigated. The research was conducted during the period of 2016–2017 under the conditions of the experimental field of the Institute for Agriculture of Polissia NAAS. in the stationary and temporary experiments, which are located on the typical sod mesopodzol sandy soils for the Polissia region. Four types of soil tillage were studied in the experiment (plowing, 18–20 cm, plowing, 12–14 cm, disc plowing, 8–10 cm, subsurface plowing, 18–20 cm) on three fertilizing backgrounds (no fertilizers, organo-mineral fertili-zation system; organic fertilization system). The experiment was laid by the method of split areas: methods of soil tillage were studied on the first-order areas with sown area of 529 m2, fertilization systems were studied on the second-order areas with an accounting area of 72 m2 . The repetition of the experiment is three -time. It has been established that yield of winter wheat depends on the soil tillage method and fertilization system. Applying field-free soil tillage methods of winter wheat yield decreased comparing to the tillage with the rotation of furrow slice, regardless of the fertilization system. The research has established that the optimal soil tillage method during winter wheat cultivation under the conditions of Polissia is plowing to a depth of 18–20 cm. The use of other investigated tillage methods results in losses of grain yield within the range of 0.08–0.56 t/ha. Fertilizers application causes increase of yield of winter wheat variety Kolos Myronivshchyny. Application of organic fertilization system contributes to increase of grain yield in the limits of 15.29–35.63%, organo-mineral system - within the limits of 28.36–44.44%, with different systems of soil tillage in comparison with the variants without fertilization. It is reasonably to plow up to a depth of 18–20 cm and use of organo-mineral fertilization system, which ensures the formation of the highest grain yield in the range of 3.96 t/ha in the conditions of Polissia of Ukraine.